SPEED CONTROLING USING DISTANCE DETECTOR IN MOVING VEHICLE (International Journal of Engineering and Computer Science, 2013)
Many accidents may be saving if emergency service detector can detect the distance between upcoming object with running vehicle, and alert the controller. This paper is proposed to provide compatibility in Doppler radar and Speedometer with EDR. This Doppler radar will monitor speed of a vehicle and compare with the inbuilt detect system of speed. We set different parameter for speed according to object availability in path and set speed criteria according to them. For measuring the distance between vehicle and object we use PLD that coupled with microcontroller.